2005
DOI: 10.1111/j.1467-6281.2005.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of accounting innovation implementation

Abstract: Accounting innovations are often not successfully implemented or diffused throughout the organization. This study seeks to explain this phenomenon. One of the major impediments to the successful implementation of accounting innovation is that management accounting systems are generally used to serve the decision control needs of top management while at the same time purportedly supporting the decision management needs of lower level managers. To the extent that the accounting system is used for decision contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 38 publications
5
97
1
8
Order By: Relevance
“…However, the examination of the operational definitions used by each study for this construct can guide us in determining the nature of decentralization studied (horizontal or vertical). Abernethy and Bouwens (2005), by the fact that decentralization choices avoid resistance to accounting innovations. These results prove the importance of employees' involvement in the use of ABC, even though Moroccan employees' skills are perceived to be low, and highlight the different motives of actors for getting involved in an ABC project.…”
Section: Discussionmentioning
confidence: 99%
“…However, the examination of the operational definitions used by each study for this construct can guide us in determining the nature of decentralization studied (horizontal or vertical). Abernethy and Bouwens (2005), by the fact that decentralization choices avoid resistance to accounting innovations. These results prove the importance of employees' involvement in the use of ABC, even though Moroccan employees' skills are perceived to be low, and highlight the different motives of actors for getting involved in an ABC project.…”
Section: Discussionmentioning
confidence: 99%
“…SMA systems require full cooperation between accountants and other functional managers in term of sharing information via MAS (Bromwich and Bhimani, 2005). Therefore, more accountants' participation in the design and implementation of MAS can promote a higher use of MAS (Abernethy and Bouwens, 2005). In addition, more accountants' participation in MAS development can result in more use of MAS from functional managers with more regular system update (Pierce and O'Dea, 2003).…”
Section: The Moderating Role Of Accountants' Participationmentioning
confidence: 99%
“…It has also been suggested that information systems support management decision-making (Abernethy and Bouwens, 2005) that can result in improved decision-making in regard to resource allocation (Baines and Langfield-Smith, 2003). In conjunction with the overall proposition of a necessary fit between CA usage, the study's contextual variables and hotel performance, it is put forth that CA practices provide important customer focused information that results in better management decision-making.…”
Section: Hotel Performancementioning
confidence: 99%